Association Study of ARMC9 Gene Variants with Vogt-Koyanagi-Harada Disease in Japanese Patients. (4th July 2019) - Ohno, Tomoko; Meguro, Akira; Takeuchi, Masaki; Yamane, Takahiro; Teshigawara, Takeshi; Kitaichi, Nobuyoshi; Horie, Yukihiro; Namba, Kenichi; Ohno, Shigeaki; Nakao, Kumiko; Sakamoto, Taiji; Sakai, Tsutomu; et al.
ABSTRACT: Purpose : To investigate whether variants in the ARMC9 gene encoding KU-MEL-1 are associated with Vogt-Koyanagi-Harada (VKH) disease in a Japanese population. Methods : We recruited 380 Japanese patients with VKH disease and 744 Japanese healthy controls to genotype seven single-nucleotide polymorphisms (SNPs) in ARMC9 . We also performed imputation analysis of the ARMC9 region and 195 imputed SNPs were included in the statistical analysis. Results : We observed an increased frequency of the A allele of rs28690417 in patients compared with controls ( P = 0.0097, odds ratio (OR) = 1.46). The A allele had a dominant effect on VKH disease risk ( P = 0.011, OR = 1.51). However, these significant differences disappeared after Bonferroni correction (corrected P > 0.05). The remaining 201 SNPs did not show any significant association with disease risk. Conclusions : Our study suggests that ARMC9 variants do not play a critical role in the development of VKH disease.